ON QoS-BASED ROUTING AND RESOURCE OPTIMIZATION - Lê, Hữu Lập (2013)
Technology and service convergence is current trend of telecommunication and the guarantee quality of service (QoS) for each application while retaining the best usage of resources is an important criterion for a such network. This leads to a QoS-based optimization process for routing (QoSR) and different aspects with respect to the said are briefly mentioned in this paper as follows: Basis of QoSR technique (II), Bandvvith-based QoSR problem (III), A proposed QoSR on MPLS-DiffServ architecture model (IV), Discussions and conclusions with respect to the proposed model (V).